International Cultural Heritage Law: A Systematic Review of Its Effectiveness - Akyazici, Merve; Turgut, Sirma (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This systematic review critically analyses the effectiveness of International Cultural Heritage Law (ICHL), with a focus on terrestrial immovable cultural heritage. Drawing on SCOPUS database sources, this study reviews existing literature on ICHL, highlighting both its strengths and limitations. The review begins by addressing the uncertainties and complexities observed in Heritage Impact Assessment (HIA) processes under the World Heritage Convention (WHC) and expands its scope to explore broader challenges in ICHL implementation. Findings from the literature suggest that while ICHL's flexibility fosters international cooperation in heritage protection, its effectiveness is hindered by limited integration into domestic legal systems, particularly when state interests. Furthermore, even within strict legal frameworks, the absence of robust institutional support and public participation undermine the sustainable management of cultural heritage. Despite ongoing uncertainties in HIA processes, existing studies continue to provide valuable yet incomplete insights into the practical application of ICHL. This review identifies critical gaps in the literature, particularly regarding the practical barriers to ICHL implementation, and recommends future research to address these challenges, aiming to improve its integration into national contexts and enhance its global effectiveness.
Keywords: International cultural heritage law; soft law; non-renewable cultural heritage resources; sustainable cultural heritage management; heritage impact assessment; PROTECTION; Arts & Humanities - Other Topics